Penegakan Hukum Lingkungan yang Seimbang (Studi Kasus Pembakaran Hutan) - Aminah AMINAH (Law Faculty of Universitas Bandar Lampung, 2018)
The environment has various functions and is very important for human life, so the Government makes legislation and enforces its law to maintain the function of the environment. Although law enforcement has been carried out, many environmental cases cannot be resolved so that pollution and environmental damage often occur in Indonesia. This research wants to know whether law enforcement in Indonesia has not yet realized the balance and how the concept of law enforcement is balanced. The approach method used by Juridical normative with analytical descriptive specifications, uses primary and secondary data and analysis using explanation building analysis. From the results of the study, it was found that Law Enforcement in Indonesia has not yet realized a balance, especially in law enforcement in cases of forest fires that have proven that forest fires repeatedly occur and have a good impact in the form of ecological impacts, economic impacts and sociological impacts, this is caused by various constraints of law enforcement Administration, civil or criminal.